Producción del Tema "Damian" del Artista "Gabo" - Tapia Reyes, Ángel Gabriel (2014)
Damian was born as a music project in February 2013, and was made due to author/producer life circumstances. Gabriel Tapia A.K.A “GABO” is an independent artist in the music industry and has the production and composing credits of this theme, “Damian” keeps the principal concept and essence to create an emotional response to the audience. The theme was made with the application of all the knowledge acquired during the learning process at the career, achieving the goal of applying the best media tools, having as a result a professional piece of music with commercial quality. It took four months to finish the producing process of “Damian”, after those, a creative and uncovered theme that successfully accomplishes the established goals was born. The musical piece was produced using twelve recording hours, eight hours of mixing, and three hours of mastering in different studios. After the producing period was finished the music piece was uploaded to internet media platforms, so that it can be played, and introduced in the music commercial market.